2019
DOI: 10.1111/cts.12681
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Knowledge and Perceptions of Pharmacogenomics Before and After Using a Mock Results Patient Web Portal

Abstract: Our objective was to build a mock pharmacogenomic (PGx) patient portal and assess its ability to disseminate test results and information to patients. The YourPGx Portal delivered four sample PGx results (omeprazole, simvastatin, clopidogrel, and codeine). We hosted two study groups to assess patient knowledge and perceptions of PGx before and after accessing the portal. Ten PGx‐tested and 10 traditional care participants were included (average 61 years, 60% women, 50% African American, and 55% had a bachelor'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Of these, 35 met eligibility criteria and were included in the analysis. An additional two articles were identified upon reference review of eligible articles and also included in the analysis, for a final total of 37 articles [ 1 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Figure 1 summarizes the identification and selection process for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 35 met eligibility criteria and were included in the analysis. An additional two articles were identified upon reference review of eligible articles and also included in the analysis, for a final total of 37 articles [ 1 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Figure 1 summarizes the identification and selection process for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Few interventions exist that can simultaneously train patients to engage more fully in the healthcare process and give providers the skills needed to activate and promote patient engagement in the care dialogue 17 . These ideas illuminate the need for additional attention to developing racially and culturally sensitive tools to educate patients about genetic risks for suboptimal drug responses 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, rather than utilizing survey measures to assess patient health literacy, we incorporated direct measures of educational status into the current study. The inclusion of direct measures assessing understanding of genetic test results is an area we are now exploring in other studies, before and after direct-to-patient delivery of pharmacogenomic test results 27 . Separately, though the absence of measures evaluating trust in providers/healthcare system among minority patients may be a limitation of some survey instruments, our survey instrument specifically measured trust, and our previous analyses of this cohort have reported that trust, defined as a patient’s belief that the provider had his or her best interest in mind when making clinical decisions, was generally high among our genotyped respondents 10 .…”
Section: Discussionmentioning
confidence: 99%
“…HealthCare have adopted transparent coverage policies for pharmacogenetic testing. 54 Pharmacists within our outside of the program can verify coverage of pharmacogenetic testing with patients' payers and/or facilitate prior authorization prior to submitting a test for reimbursement. For example, Cleveland Clinic Health System partners with an external laboratory to provide prior authorization services.…”
Section: Reimbursement For the Pharmacogenetic Testmentioning
confidence: 99%